Escherichia coli NusG protein stimulates transcription elongation rates in vivo and in vitro. - Burova, E (1995)
The rate of transcription elongation in Escherichia coli was reduced when cells were depleted of NusG. In a purified in vitro system, NusG accelerated the transcription elongation rate. The stimulation of the rate of transcription elongation by NusG appears to result from the suppression of specific transcription pause sites.